2023
DOI: 10.3389/fmicb.2023.1060282
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ginsenosides on microbial community and enzyme activity in continuous cropping soil of ginseng

Abstract: Root exudates contain plant metabolites secreted by the roots into the soil, such as ginsenosides secreted by the ginseng root. However, little is known about ginseng root exudate and its impact on the chemical and microbial properties of soil. In this study, the effect of increasing concentrations of ginsenosides on the chemical and microbial properties of soil was tested. Chemical analysis and high-throughput sequencing techniques were used to evaluate the soil chemical properties and microbial characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…For example, it has been shown that root exudates (oleamide, hexadecanamide, ethanolamine, etc.) act as a source of carbon and nitrogen, and their release and accumulation enhance competition between pathogens and other microorganisms and hinder healthy plant growth ( Miao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that root exudates (oleamide, hexadecanamide, ethanolamine, etc.) act as a source of carbon and nitrogen, and their release and accumulation enhance competition between pathogens and other microorganisms and hinder healthy plant growth ( Miao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The available nitrogen (AN), available phosphorus (AP), available potassium (AK), and OM contents were measured following the instructions of the Kjeldahl method, the molybdenum antimony anti-chromogenic extraction method, inductively coupled plasma (ICP) spectrometer method, and the K2Cr2O7-H2SO4 oxidation approach (Zhao et al, 2020), respectively. Urease (UE), sucrase (SC), and peroxidase (POD) activities were measured using the phenol sodium hypochlorite colorimetric method, the 3,5-dinitrosalicylic acid colorimetric method, and spectrophotometry method (Jia, 2016), respectively.…”
Section: Soil Properties and Enzymatic Activitymentioning
confidence: 99%
“…He et al (2009) reported that the presence of fungal pathogens in the soil causes replanting disease of American ginseng. The solution to this problem according to the research of Miao et al (2023) is to use ginsenosides as allelopathic growth stimulants of fungal pathogens in the rhizosphere. In addition, other studies have also reported that ginsenosides reduce soil-borne diseases.…”
Section: Introductionmentioning
confidence: 99%